Ta'arud Al-Adillah Dan Tanawu' Dalam Ibadah : Tinjauan Tentang Bacaan Basmalah Dalam Salat - Syamsul Anwar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
This article deals with one of the important concepts of u??l al-fiqh(Islamic legal theories), i.e. conflict of proofs of law, and its relation to theplurality of ways in performing Islamic worship with special reference to the case of reciting basmalahin prayer and at the same time deals with the authentication of the related prophetic traditions. There are disagreements among the u??l?s regarding the steps to be followed in settling the conflict of proofs of law: should one place the compromise method at the head or should he make the obrigation or the weighing one preced? Forwarding the compromise method enables a wider acceptance of applying principle of plurality in worship performance so that different opinions can be appreciated.